Gender Diversity of Boards, Board Composition and Firm Performance - Mandala, Nebert; Kaijage, Erasmus; Aduda, Josiah; Iraya, Cyrus (European Scientific Journal, ESJ, 2017)
The broad objective of this research was to determine whether gender diversity of boards and board composition, affects performance. Secondary data was collected for a ten-year period from 2006 to 2015 from 98 sampled financial institutions. Multiple regression analysis and generalized estimating equations were used in analysis of the collected data. Parametric and nonparametric methodologies were used. The study was anchored on the agency theory, stakeholder theory, the human capital theory and resource dependence theory. The results show that, gender diversity of boards and board composition had no independent significant influence on performance of financial institutions. Through the study formulation of managerial policy and practice that promote better governance practices and appropriate firm characteristics that improve performance of financial institutions will be enhanced.